PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII1 SMPN 1 PASIR PENYU - Mia Septiani Putri; Putri Yuanita; Maimunah Maimunah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted due to the student’s outcomes learning of class VIII1 SMPN 1 Pasir Penyu and the number of students who achieved the Minimal Score of Criteria is still low. This research is a classroom action research that aims to improve the learning process and to increase the outcomes of mathematics learning of the students by implementation of realistic mathematics education approach. The subjects of this research were 28 students of class VIII1 SMPN 1 Pasir Penyu at the first semester of academic year 2018/2019. This research has two cycles. Each of them has four stages: planning, implementation, observation, and reflection. The research instrument consists of learning instruments and instruments of collecting data. The Learning instruments used include syllabus, lesson plans, and student worksheets. While the instruments of collecting data covered observation sheets were used to find out the data of students and teacher activity during learning process, and outcomes of mathematic learning tests used to collect the student’s outcomes of mathematics learning data. The data were analyzed by narrative descriptive and statistical descriptive analysis. Based on the analysis of the observation Osheets showed that implementation the realistic mathematics educations of learning process on cycle II had happened improvement from implementation on cycle I. While from statistical descriptive analysis showed that the number of students who reach the A and B predicate, increased from the basic score to the cycle I, and from cycle I to cycle II. The percentage of students who achieved the Minimal Score of Criteria is increase. In conclusion, the implementation of realistic mathematics educations improved the learning process and the student’s outcomes of mathematics learning of grade VIII1 SMPN 1 Pasir Penyu on the first semester in academic years 2018/2019.Key Words: Realistic mathematics educations, outcomes of mathematic learning, learningactivity